Spiral Cognition: Epistemological Grounds - Vovk Olena (Pedagogical Discourse, 2015)
The article focuses on the bases of multiparadigmatic spiral cognition. In particular, levels and ways of cognition have been examined, the mechanisms of cognitive activity have been traced. The importance of gnoseological pluralism has been cleared out, according to which combination of rational, sensual, and experience in cognitive process is postulated. The idea of interaction of different formations and paradigms of cognition, resulted in creation of multiparadigmatic epistemological systems has been accentuated. The spiral model of knowledge acquisition has been offered.